Hidden challenges: An invisible disabilities learning activity - Nicole Bérubé (Organization Management Journal (OMJ), 2024)
Purpose This paper aims to describe an experiential learning activity designed to sensitize students to the prevalence and challenges of disclosing invisible disabilities in the workplace. It provides an impactful learning experience about a widespread phenomenon that receives little attention in textbooks. Design/methodology/approach The exercise assigns a hidden disability to some participants who interact with others who act as trusted friends. The interactions help participants develop their ability to interact sensitively with those who may have hidden disabilities. They explore the advantages and disadvantages of disclosing hidden disabilities at work. Guiding questions help focus deliberations during which participants consider the influence of their assigned role. Findings A plenary discussion follows where students share the outcomes of the simulation. Debriefing questions and suggested answers help instructors deepen student learning on the topic. A follow-up assignment allows participants to summarize personal learning about the subject and solidify the learning outcomes. Originality/value Most workers with nonapparent disabilities hide them, although disclosing them may help their employers provide helpful accommodations. This learning activity helps increase awareness and understanding of hidden disabilities in work settings and supports learning about disclosing and accommodating disabilities in the workplace. Instructors can use the activity to support understanding of employee rights, equity and accommodations in large or small classes, in-person or online, synchronously or asynchronously.
Keywords: 650; Experiential learning; Inclusion; Invisible disabilities; Simulation; Workplace accommodations